Prevalensi, Intensitas, dan Dominansi Parasit pada Ikan Manggabai (Glossogobius giuris) di Danau Limboto Provinsi Gorontalo - Alia Hamid; Djuna Lamondo; Regina Valentine Aydalina (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aimed to identify the different types of parasites infecting manggabai fish (Glossogobius giurus) in Lake Limboto, in addition to analyzing the intensity, prevalence, and dominance of parasites in the population. Twenty manggabai fish samples were collected from three different locations in Lake Limboto, namely Dembe 1, Tabmela, and Hutuo. The parasite examination process was carried out at the Zoology Laboratory of the Biology Department of Gorontalo State University, focusing on organs such as skin, gills, fins, and digestive organs. The method applied was the native method, which involves direct observation. The identification results showed the presence of three types of parasites in manggabai fish, namely Gyrodactylus sp., Camallanus sp., and Ligula intestinalis. The highest prevalence was recorded for Gyrodactylus sp. at 65%, indicating a significant spread of parasites in the fish population. The parasite intensity of Camallanus sp. from Hutuo at 7. The parasite Ligula intestinalis showed the highest dominance with a value of 44%. Meanwhile, the highest prevalence and intensity values were placed in the frequent and mild categories.